2006
DOI: 10.1002/hep.21169
|View full text |Cite
|
Sign up to set email alerts
|

Bile salt toxicity aggravates cold ischemic injury of bile ducts after liver transplantation in Mdr2 +/− mice

Abstract: Intrahepatic bile duct strictures are a serious complication after orthotopic liver transplantation (OLT). We examined the role of endogenous bile salt toxicity in the pathogenesis of bile duct injury after OLT. Livers from wild-type mice and mice heterozygous for disruption of the multidrug resistance 2 Mdr2 gene (Mdr2؉/؊) were transplanted into wild-type recipient mice. Mdr2؉/؊ mice secrete only 50% of the normal amount of phospholipids into their bile, leading to an abnormally high bile salt/phospholipid ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 39 publications
(45 reference statements)
1
25
0
Order By: Relevance
“…29 Factors that lead to such damage may include prolonged warm and cold ischemia times 30 ; older age of the donor 31 ; preservation injury 31,32 ; immunological factors such as ABO incompatibility, chronic rejection, and chemokine 5⌬32 polymorphism 33 ; and bile salt toxicity. 34 The frequency of ITBLs in liver transplantation is reported to be in the range of 5% to 10%, 30,35 and therefore the incidence of 7.8% in our study is in accord with the literature. In our study, ITBLs were diagnosed a median of 8 months after liver transplantation, which is slightly later than the 6 months reported in other series.…”
Section: Discussionsupporting
confidence: 93%
“…29 Factors that lead to such damage may include prolonged warm and cold ischemia times 30 ; older age of the donor 31 ; preservation injury 31,32 ; immunological factors such as ABO incompatibility, chronic rejection, and chemokine 5⌬32 polymorphism 33 ; and bile salt toxicity. 34 The frequency of ITBLs in liver transplantation is reported to be in the range of 5% to 10%, 30,35 and therefore the incidence of 7.8% in our study is in accord with the literature. In our study, ITBLs were diagnosed a median of 8 months after liver transplantation, which is slightly later than the 6 months reported in other series.…”
Section: Discussionsupporting
confidence: 93%
“…21 Alteration of the transmembrane Cl À gradient, driving HCO À 3 secretion, or altered flux of HCO À 3 via a dysfunctional cystic fibrosis transmembrane conductance regulator, CFTR, might be the basis for the development of cystic-fibrosis-associated liver disease, which may resemble sclerosing cholangitis. 23 Ischemia-type biliary lesions and nonanastomotic bile duct strictures after liver transplantation with denervation in man 42 may be a consequence of disrupted vagal acetylcholine signaling, a physiologic driving force of biliary HCO À Our data may have particular impact on the understanding of the pathogenesis and treatment of PBC. [17][18][19][20]39,43 Increasing evidence supports the view that cholangiocyte apoptosis is a driving force in the pathogenesis of PBC: It has long been demonstrated that cholangiocyte apoptosis is associated with ductular inflammation in PBC, but not PSC.…”
Section: Discussionmentioning
confidence: 89%
“…The substantial decrease observed in the phospholipid:bile salt ratio in the CC group indicates an increase in the cytotoxicity of the bile fluid [28,29,31,32]. This may be partly responsible for subsequent hepatocyte injury and impaired liver function [cf.…”
Section: Discussionmentioning
confidence: 99%